Personal Support Worker (PSW)‐supported home hemodialysis: A paradigm shift. Issue 2 (22nd August 2016) - Pierratos, Andreas; Tremblay, Melanie; Kandasamy, Gokulan; Woodward, Graham; Blake, Peter; Graham, Janet; Hebert, Marc; Harvey, Rebecca
Abstract: Introduction: Despite improving clinical outcomes associated with the use of home hemodialysis (HD), its utilization is low in most countries. The inability or unwillingness of patients and their families to participate in their own treatment is one of the most important barriers to the adoption of home HD. Methods: We hypothesized that paid helper‐delivered home HD supported by public funds would be successful and welcomed by patients and be delivered at an affordable cost. We conducted a pilot project to dialyze six patients at home using Personal Support Workers (PSW) and resolve regulatory, organizational and financial constraints. Findings: cWe provided publically‐funded PSW‐supported home HD to six patients. We describe the administrative structure of the pilot project allowing scalability and turnkey operation in the province of Ontario. Regulatory and insurance concerns were resolved and patients and staff were enthusiastic. The projected total dialysis cost, when economies of scale are met, are expected to be lower than the cost of in‐center HD. Discussion: A second phase of the project is currently under way including 8 hospitals and 67 patients. If equally successful, it may have significant implications for the delivery of care for End Stage Renal Disease in Ontario and similar jurisdictions. It promises to increase the utilization of home dialysis possibly at a lower cost than in‐center HD. This would be particularly important in providing dialysis in underserviced and geographically hard to access areas.